Experimental study of the influence of particle size on Minimum Explosible Concentration of sulfur dust - Jack M. Altwal (17302843) (2021)
Despite the extensive use of sulfur in the industry, very little information is available in the literature on its key dust explosion properties. The work presented in this paper contributes to filling the current knowledge gaps on sulfur dust explosion properties and focuses on the experimental determination of the MEC of sulfur dust using a Modified Hartmann Tube and a 20 L dust explosion sphere. First, the MEC of sulfur dust samples collected at a sulfur production facility from areas prone to the generation of fine sulfur dust was measured. The results showed that these sulfur dust samples are fine enough to cause dust explosions with 55 ± 5< MEC <105 ± 5 g/m3. Second, the influence of the particle size of sulfur dust was investigated with both equipment. The use of the Modified Hartmann Tube for MEC determination showed that the MEC increases with increasing particle size in the particle size range of 0–2000 μm. Unlike the Modified Hartmann Tube, MEC experiments done in the 20 L Sphere did not allow the quantification of the influence of the particle size on the MEC. These results were explained by the phenomenon of particle breakage induced by the 20 L Sphere's dispersion mechanism. Additional experiments with the 20 L sphere confirmed the particle breakage of sulfur dust particles and showed that it is inversely proportional to dust concentration and proportional to the dust's original particle size distribution. Other Information Published in: Journal of Loss Prevention in the Process Industries License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.jlp.2021.104507